A formulation of conditional states on steganalysis approach - Din, Roshidi; Che Ani, Zhamri; Samsudin, Azman (WSEAS, 2012)
In this paper, we present a consolidated formulation of conditional states from the perspective of steganalysis approach.It has been identified that the conditional states used in steganalysis approach include hypothesis testing, gaussion distribution, hidden markov model and vector analysis space. The main objective of this paper is to find the best approach to fit in using mathematical formulation for steganalytic system based on these conditional states. It is found that there is a boundary of solution between the steganalytic system and analyzed message.